Nutritional and motor functional status in Parkinson’s disease: the NutriSPark protocol - Grunho, Miguel; Godinho, Catarina; Sousa-Catita, Diogo; Vicente, Filipa; Proença, Luís; Carregosa, Ricardo; Marx, Frederico; Tomé, Morgane; Domingos, Josefa; Fonseca, Jorge (MDPI, 2021)
A growing body of evidence suggests that nutritional status may play an important role in the development and course of Parkinson’s disease (PD). Nutritional status is known to influence PD motor and non-motor features and is in turn influenced by disease duration and severity. A proper nutritional status assessment and intervention should be incorporated in the management and follow-up of PD patients. This study aims to characterize the impact of nutritional status in multiple domains of PD and to explore the feasibility and the effectiveness of a customized and intensive nutritional intervention compared to standard care.
Communication abstract: Proceedings of the 5th International Congress of CiiEM - Reducing inequalities in Health and Society, held at Egas Moniz’ University Campus in Monte de Caparica, Almada, from June 16th to 18th, 2021.
This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Parkinson’s disease; Nutritional status; Motor function